Reasons Justifying the Need to Require First-order Quantificational Logic on Admissions Exams Preparation Manuals for State Universities in Lima, Peru - Mora Ramirez, Rafael Félix (2019)
This study the Aristotelian logic requirement included on the admissions exams in eight of the eleven state universities in Lima, Peru. A comparison of Aristotelian logic and quantificational first-degree logic revealed the shortcomings of the former versus the latter after analyzing the syllabi of the following state university departments: Engineering  at the National University of Callao, Education at the  Enrique Guzman y Valle National University and the José Faustino Sánchez Carrion University; and Technology at the National Technological University of South Lima, the National University of Cañete and the National University of Barranca. All content dealing with Aristotelian logic was extracted from the manual used by test preparation centers to teach prospective applicants. The objective was to determine contradictions and faults found in first-order quantificational logic questions. A qualitative analysis was performed  through a literature review. Research for the logic in this study is divided into 1) Aristotelian Logic 2) Class Logic, 3) First-Order Quantifiable Logic, 4) Boethius Traditional Square of Opposition, 5) Special recommendations, 6) Immediate inferences based on operations and 7) Categorical Syllogisms. it is concluded that quantifiable first-order logic has progressed significantly within the study of logic, that it must be included within the areas to be studied within the Admissions exams for universities in Lima-Peru. There is a need for empirical research to fill any gaps found in this study.